2018
DOI: 10.7717/peerj.4900
|View full text |Cite
|
Sign up to set email alerts
|

A new species of spotted leaf frog, genusPhasmahyla(Amphibia, Phyllomedusidae) from Southeast Brazil

Abstract: Based on concordant differences in male advertisement call, tadpole morphology, and absence of haplotype sharing in the barcoding 16S mitochondrial DNA, we describe here a new species of spotted leaf frog of the genus Phasmahyla from Atlantic Forest, State of Rio de Janeiro, Southeast Brazil. The new species is most similar to P. cochranae (type locality) and P. spectabilis (type locality). It differs from these species by the size of the calcar, moderate-sized body (snout-vent length 30.4–34.4 mm in adult eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Before our work, vocalizations of species in the genus Phasmahyla was only known for three species (out of eight): Phasmahyla spectabilis (Dias et al, 2011), Phasmahyla timbo (Cruz, Napoli & Fonseca, 2008), and Phasmahyla lisbella (Pereira et al, 2018). Calls of these three species are very similar to those of Phasmahyla cochranae and Phasmahyla jandaia .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before our work, vocalizations of species in the genus Phasmahyla was only known for three species (out of eight): Phasmahyla spectabilis (Dias et al, 2011), Phasmahyla timbo (Cruz, Napoli & Fonseca, 2008), and Phasmahyla lisbella (Pereira et al, 2018). Calls of these three species are very similar to those of Phasmahyla cochranae and Phasmahyla jandaia .…”
Section: Discussionmentioning
confidence: 99%
“…Calls of these three species are very similar to those of Phasmahyla cochranae and Phasmahyla jandaia . All five species have calls composed by a single note with non-fused pulses (Cruz, Napoli & Fonseca, 2008; Dias et al, 2011; Pereira et al, 2018). Phasmahyla jandaia has the longest notes (achieving 0.09 s), while Phasmahyla spectabilis and Phasmahyla timbo have notes around 0.03 s (Cruz, Napoli & Fonseca, 2008; Dias et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Integrative Taxonomy approach [ 20 ] highlighted the importance of morphological features associated with different data sources, which was exemplified in several anuran groups [ 1 , 10 , 21 ]. The importance of combining more than one data source in Brachycephalus studies is related to the recent species divergence [ 22 24 ], granting the use of multiple lines of evidence as morphology [ 22 ], osteology [ 25 , 26 ], bioacoustics [ 27 , 28 ] and molecular identity [ 9 ] a gold standard approach for the delimitation of species of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…Combining different approaches (e.g., morphological, bioacoustic, population genetics, ecology) have been successfully used to delimit new species in the Neotropics (e.g., Andrade et al, 2019;Mângia et al, 2018;Pereira et al, 2018), and revealed new taxa within many species complexes traditionally classified as a single nominal organism (Fouquet et al, 2012a;Fouquet et al, 2014;Gehara et al, 2013). Although the megadiverse Amazon Forest biome harbors many species that are widespread, many anurans are philopatric with poor dispersal abilities, which frequently results in strong genetic structure and allopatric distributions (Funk, Caminer & Ron, 2012;Pirani et al, 2020;Vacher et al, 2017).…”
Section: Introductionmentioning
confidence: 99%